Tradeoffs around crop residue biomass in smallholder crop-livestock systems - Whatïs next? - Tittonell, Pablo Adrian (2015)
Much has been written on the tradeoffs that smallholder farmers face when having to allocate their biomass resources among competing objectives such as feed, fuel, mulch, compost or the market. This paper summarises yet a new body of evidence from 10 studies on tradeoffs in the allocation of cereal crop residue biomass between soil management and livestock feeding in developing regions, published in the special issue of Agricultural Systems ‘Biomass use tradeoffs in cereal cropping systems: Lessons and implications from the developing world’. The studies cover a diversity of socio-ecological contexts, farming system types and scales of analysis. We reflect on their main findings and methodological progress, and on the new and not-so-new implications of these findings for research and action in the development agenda. We propose stylised graphical models to portray tradeoffs and plausible trajectories towards synergies, in the hope that such generalisations would prevent further efforts to ‘reinvent the wheel’ in the realm of tradeoffs analysis. We advocate an ex-post impact assessment of recent investments in systems research to help focus such research further and clearly define its future role in prioritizing and targeting development interventions.